Óleos essenciais de plantas medicinais: estudo químico e avaliação biológica da atividade biológica das espécies Allophylus edulis e Guarea macrophylla - Ribeiro Filho, Waldemar Alves [UNIFESP] (2014)
The plant species are a number of sources of volatile substances of low molecular mass, known as secondary metabolites or natural products. The use of many of these metabolites, such as pharmaceuticals or antifungal agents has stimulated research on the plant species to be described from the point of view phytochemical by the pharmaceutical and agrochemical industries. Many of the drugs used in therapy today are derived from plants, and the search for species with antimicrobial and antitumor properties have been intensified in recent years due to the increasing problems associated with the use of various antibiotics. This project aims to study the chemical and biological evaluation of essential oils extracted from two plant species: Allophylus edulis and Guarea macrophylla. This work included the collection of plant species, obtaining essential oils from fresh leaves by hydrodistillation in Clevenger type apparatus, the identification of the chemical constituents and evaluation of antimicrobial and cytotoxic activities. Plants were selected taking into consideration the accessibility and availability of the Parque Estadual da Serra do Mar - Itutinga - Pilões in the city of Cubatão, and in the case of A. edulis, weighed up the lack of scientific studies detailing the chemical composition of volatile oils and biological activity. Gas chromatography was chosen as the analytical technique to effect the separation of the chemical constituents and mass spectrometry for identification and quantification of them. As a parameter for this determination was proposed the use of Kovatz Retention Index (KI), which compares the retention time of a complex mixture with the retention time of a series of alkanes, allowing for a later comparison with values tabulated in the literature. For the first time it was performed the analysis of the chemical composition of the essential oils of A. edulis. Evaluated for antimicrobial activity, essential oils of the two species were inactive. Regarding the evaluation of the cytotoxic potential of the species A. edulis and G. macrophylla showed good activity against the murine melanoma B16F10-Nex2.